Drivers of productivity change in global value chains: Reallocation vs. innovation - Philipp Mundt; Ivan Savin (Bamberg University, Bamberg Economic Research Group (BERG), 2022)
We revisit the debate on the role of technological improvement and market share reallocation in determining aggregate productivity gains. Contrary to previous work that neglects dependencies between suppliers in global value chains, we explicitly account for input linkages that impact both channels of productivity improvement. Using sector-level data from the World Input-Output Database, we show that market share reallocation has a markedly larger effect on productivity change than innovation.
Keywords: C67; E24; L14; L16; O47; 330; input-output analysis; market share reallocation; productivity decomposition; production network; technological improvement